2011
DOI: 10.1021/ja1076537
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Reductive Radical Formation and Electron Recycling in (R)-2-Hydroxyisocaproyl-CoA Dehydratase

Abstract: The radical enzyme (R)-2-hydroxyisocaproyl-CoA dehydratase catalyzes the dehydration of (R)-2-hydroxyisocaproyl-CoA in the fermentation of l-leucine by the human pathogenic bacterium Clostridium difficile. In contrast to other radical enzymes, such as bacterial class II ribonucleotide reductase or biotin synthase, the Fe/S cluster containing (R)-2-hydroxyisocaproyl-CoA dehydratase requires no special cofactors such as coenzyme B(12) or S-adenosylmethionine for radical generation. Instead it uses a single high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
81
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 41 publications
(85 reference statements)
4
81
0
1
Order By: Relevance
“…Third, the cluster of TtuA is ligated by only three cysteines and thus, has a free coordination site on the fourth iron, which can be occupied by a hydrosulfide ligand. Precedents for exogenous sulfur species bound to an iron site of a [4Fe-4S] cluster have been reported: a comparable [4Fe-5S] cluster has been observed in HydG, an enzyme involved in maturation of hydrogenases (17), as well as 2-hydroxyisocaproyl-CoA dehydratase (18). Moreover, in the structure of the methylthiotransferase RimO, a polysulfide terminal ligand to a [4Fe-4S] cluster has been observed (19).…”
Section: Discussionmentioning
confidence: 95%
“…Third, the cluster of TtuA is ligated by only three cysteines and thus, has a free coordination site on the fourth iron, which can be occupied by a hydrosulfide ligand. Precedents for exogenous sulfur species bound to an iron site of a [4Fe-4S] cluster have been reported: a comparable [4Fe-5S] cluster has been observed in HydG, an enzyme involved in maturation of hydrogenases (17), as well as 2-hydroxyisocaproyl-CoA dehydratase (18). Moreover, in the structure of the methylthiotransferase RimO, a polysulfide terminal ligand to a [4Fe-4S] cluster has been observed (19).…”
Section: Discussionmentioning
confidence: 95%
“…T here are numerous examples where radicals play key roles in the active site of enzymes [1][2][3][4][5][6][7][8][9][10][11][12]. These radicals are normally located on a reactive amino acid side chain (cysteine [2], methionine, tyrosine, or tryptophan [10]) or on the peptide backbone, namely at the α-carbon positon of glycine [13].…”
Section: Introductionmentioning
confidence: 99%
“…These radicals are normally located on a reactive amino acid side chain (cysteine [2], methionine, tyrosine, or tryptophan [10]) or on the peptide backbone, namely at the α-carbon positon of glycine [13]. In some instances, it has also been shown that the radical migrates to different positions in the inactive form [4,5,9]. In those cases, the radical is relocated to the less reactive positions of the sulfur atom on a cysteine residue [4,5,9] or to the glycine α-carbon [6,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The binding of two MgATP molecules to the reduced activator is supposed to induce a conformational change and drives formation of the complex with the dehydratase. ATP hydrolysis likely increases the reducing power of the reduced [4Fe-4S] cluster of the activator, enabling the one-electron transfer to the low-potential [4Fe-4S] cluster of the dehydratase (2,15). Unlike the 2-hydroxyacyl-CoA dehydratase system, the reduction of benzoyl-CoA is a two-step ETrequiring a stoichiometric consumption of ATP (3).…”
mentioning
confidence: 99%